Proximate analysis and safety profile of farmed edible bird’s nest in Malaysia and its effect on cancer cells - Tan, Sin Nee (2018)
Edible bird’s nest (EBN), a solidified swiftlet's saliva, is the most valuable animal products consumed by human in Asia. EBN was documented to contain high nutritional values and various medicinal properties. Good nutritional profile containing high protein, carbohydrate, fat, and trace elements found in EBN have been well established from previous studies done in different countries in Malaysia, Indonesia and Thailand. However, the previous proximate analysis studies of Malaysia EBN were not representative from all the regions in Malaysia. In recent years, many safety issues which included high nitrate and nitrite contents, presence of heavy metal, fungal infection and cancer cell stimulation in vitro were also found to be associated with EBN. Although the EBN are known to be dirtier during haze period as the saliva from the swiftlet are contaminated from air pollution, there has been no prior study to assess the effect on haze towards the quality of EBN. Hence, this study was carried out to determine the proximate analysis, safety profile during normal and haze period, and its effect on cancer cells of farmed EBN in Malaysia. Seven raw cleaned EBN samples were sourced from 6 different regions in Malaysia. Proximate analysis and were performed by using official AOCA methods according to the Malaysia Standard MS 2509:2012. This study showed a consistency of high protein (53.03%-56.37%) and carbohydrate (27.97%-31.68%) with acceptable level of moisture (10.8-14.04%) and ash (2.22%-3.38%). Besides that, a good safety profile was obtained with low nitrite and nitrate level, undetectable heavy metals and no significant growth for pathogenic microorganism. However, this study had found above tolerance level of mould in EBN. Haze contaminated EBN exhibited no significant differences in terms of nutritional, heavy metal and microorganism profiles. The presence of epidermal growth factor (EGF) like peptides was postulated as the important key of cancer cell stimulation. Chicken EGF Enzyme-linked immunosorbent assay (ELISA) was used for quantification of EGF content. In this study, EGF (30.7 pg/mL and 74.5 pg/mL) were detected in crude EBN 01 (Rompin) and EBN 02 (Sibu), respectively but not in all digested EBN samples and even after post 10 times concentrated EBN extract. However, both the results were below quantification level. Microculture tetrazolium assay (MTT) was carried out for the assessment of growth stimulation by different concentration of human EGF (hEGF) in comparison to EBN in 4 different cancer cell lines: MCF-7, Caco-2, HCT116, and A549 for 24, 48, and 72 h. Cancer cell growth was significantly increased after treatment with hEGF. However no significant cell growth was observed after treatment with EBN. In conclusion, EBN in Malaysia has good consistency of nutritional profile, free from heavy metals, within tolerance level of nitrate and nitrite, and also microorganism profile except mould content. Furthermore, in vitro study indicated that EBN is not associated with cancer cell growth stimulation.